Spectrophotometric Determination of Chlorpromazine â€“ HCl Using Potassium Permanganate - B. Dikran, Sarmad; K. Mohammed, Alaa; S. Hammodi, Azhar (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Twosimple, sensitive,accurate, and precise spectrophotometric methods have been developed for the determination of chlorpromazine â€“ HCl in pure form and pharmaceutical formulation. The first method involved treatment of cited drug with a measured excess of permanganate in acid medium and the unreacted oxidant was measured at 525 nm. The second method involves the reaction  of the drug with potassium permanganate in the presence of sodium hydroxide to produce a bluish â€“ green  colored manganite which is measurable at 610nm. All the experimental variables affecting the development of the manganite ions were investigatedand conditions were optimized. Working linearity ranges were 5-45 Âµg.mL-1and 1-20 Âµg.mL-1 by two   methods   respectively. The apparent molarabsorptivities are 4.015 ï‚´ 103and 18.717ï‚´ 103L.mol-1.cm-1 respectively, with corresponding Sandellâ€™s sensitivityvalues of0.0885and 0.01798Âµg.cm-2 respectively. The methods have successfully been applied to the determinationof drug in dosage forms.